A Chromosome-Level Assembly of Blunt Snout Bream (Megalobrama amblycephala) Genome Reveals an Expansion of Olfactory Receptor Genes in Freshwater Fish. (18th May 2021) - Liu, Han; Chen, Chunhai; Lv, Maolin; Liu, Ning; Hu, Yafei; Zhang, Hailin; Enbody, Erik D; Gao, Zexia; Andersson, Leif; Wang, Weimin
Abstract: The number of olfactory receptor genes (ORs ), which are responsible for detecting diverse odor molecules varies extensively among mammals as a result of frequent gene gains and losses that contribute to olfactory specialization. However, how OR expansions/contractions in fish are influenced by habitat and feeding habit and which OR subfamilies are important in each ecological niche is unknown. Here, we report a major OR expansion in a freshwater herbivorous fish, Megalobrama amblycephala, using a highly contiguous, chromosome-level assembly. We evaluate the possible contribution of OR expansion to habitat and feeding specialization by comparing the OR repertoire in 28 phylogenetically and ecologically diverse teleosts. In total, we analyzed > 4, 000 ORs including 3, 253 intact, 122 truncated, and 913 pseudogenes. The number of intact ORs is highly variable ranging from 20 to 279. We estimate that the most recent common ancestor of Osteichthyes had 62 intact ORs, which declined in most lineages except the freshwater Otophysa clade that has a substantial expansion in subfamily β and ε ORs . Across teleosts, we found a strong association between duplications of β and ε ORs and freshwater habitat. Nearly, all ORs were expressed in the olfactory epithelium (OE) in three tested fish species. Specifically, all the expanded β and ε ORs were highly expressed in OE of M. amblycephala . Together, we provide molecular and functional evidence for how OR repertoires in fish have undergone gain and loss with respect to ecological factors and highlight the role of β and ε OR in freshwater adaptation.